2008
DOI: 10.1093/jjco/hyn041
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan Plus Cisplatin for Therapy of Small-cell Carcinoma of the Esophagus: Report of 12 Cases from Single Institution Experience

Abstract: To our knowledge, this is the first report of the series of more than 10 patients with small-cell carcinoma of the esophagus treated with the same chemotherapy regimen. The combination of CPT-11 and CDDP appears to be effective therapy of this disease with acceptable toxicity profile. We believe that this regimen is one of the options to be considered for treatment of esophageal small-cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 17 publications
2
40
0
Order By: Relevance
“…Many authors reported that systemic chemotherapy with or without local treatment such as radiotherapy should be regarded as important treatment options for esophageal ECC 1,8,9) . Chemotherapy consisting of CPT -11 8) or etoposide 9) plus platinum such as cisplatin or carboplatin is effective for esophageal ECC. Such therapy is the standard regimen for small cell carcinoma of the lung.…”
Section: Case Reportmentioning
confidence: 99%
“…Many authors reported that systemic chemotherapy with or without local treatment such as radiotherapy should be regarded as important treatment options for esophageal ECC 1,8,9) . Chemotherapy consisting of CPT -11 8) or etoposide 9) plus platinum such as cisplatin or carboplatin is effective for esophageal ECC. Such therapy is the standard regimen for small cell carcinoma of the lung.…”
Section: Case Reportmentioning
confidence: 99%
“…Alcohol and smoking are commonly regarded as potential risk factors, but no clear correlations have been demonstrated in previous epidemiological studies. 6 17 27 We report an octogenarian patient with SCCE who has achieved complete remission lasting more than 1 …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In addition, SCCE displays 26 Few reports of large series have been reported to date because of the rarity of this entity. Optimal treatment for this tumor has yet to be defined, because of the lack of any comprehensive description of SCCE, and surgery, chemotherapy, radiotherapy, or a combination might be performed empirically, with no promise of efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,5,9,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The baseline characteristics of all patients are shown in Table 1. The characteristics of patients from our institution are summarized in Table 2.…”
mentioning
confidence: 99%